PERFORMANCES OF POPULATIONS OF SEX REVERSED TILAPIA AND GENETICALLY MALE TILAPIA IN FINGERLING PONDS - Didik Ariyanto; Nunuk Listiyowati; Yogi Himawan (Indonesian Aquaculture Journal, 2009)
One of the most popular techniques in mass production of all or nearly all male tilapia population is through sex reversal. However, cross mating of YY super male with regular brood-stock is gaining popularity and has been practiced by aqua-culturists. This study was conducted to evaluate the performance of 2 populations of sex reversed tilapia (sex reversed with dietary application of 17-α methyl testosterone, SRT-1, and sex reversed with dietary administration of imidazole, SRT-2) and 1 population of genetically male tilapia (GMT) derived from YY super male until the end of fingerling rearing period. Mixed sex tilapia (MST) derived from normal mating was used as the control population. The results showed that the daily growth rates of SRT-1, SRT-2, GMT, and MST were 0.12, 0.11, 0.20, and 0.07 g/day, with survival rates were 57.83%, 64.67%, 39.67%, and 68.78%, respectively. The GMT has higher harvest yield than the other populations; SRT-1 (+15.73%), SRT-2 (+6.37%), and MST (+20.82%).